Evaluation of Frankliniella occidentalis (Thysanoptera: Thripidae) sex ratio in crops by two monitoring methods - Mateus, C.=700 1 Araéjo, J.; Mexia, A.
Resumenes (Es, En)
9 tab; 16 ref.
Keywords: FRANKLINIELLA OCCIDENTALIS; CAPTURA ANIMAL; TRAMPAS; MUESTREO; PROPORCION DE LOS SEXOS; TRAMPAS ADHESIVAS AZULES